Ano ba talaga kuya!?! the role of kinship terms in the power play among sibling relationships - Emboltura, Anna Salientes 1979-; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This is a qualitative study on the significance of sibling terms in sibling relationships with thirty respondents divided under the category of birth order (eldest, middle, youngest) and social class (upper, lower, middle). Twelve respondents were from the middle class, nine from lower class and another nine from the upper class. The sample was further divided into three for every position of birth order: There were ten eldest, ten middle, and ten youngest siblings. The study used Focus Interview as the method of the study and also used thematic analysis to locate themes that present the significance of sibling addresses. The objective of the study is to find out the significance of sibling terms in sibling relationships. Whether or not sibling addresses contribute in the power play among sibling members, it was the aim of the study to probe on its significance. The study located five themes in presenting the significance of sibling titles in sibling relationships. The five main themes are "Ate" and "Kuya" as: A) Symbol of respect, B) Assertion of authority, C) Implication of responsibilities, D) Conforming to norms of Philippine society, E) Closer relationship with siblings. Based on the responses of the informants, it appeared that sibling terms were viewed as agents of respect that served to benefit the relationship of siblings. Sibling terms function to offer a well-deserved treatment for the elder members and a better way for the younger ones to establish ties with their siblings. Regarding power distribution among siblings, it is said that siblings are supposed to acquire equal status in family relationships. But more often than not, siblings take different roles to portray and responsibilities to attend to in family relationships, thus creating a structure among sibling members. It is very clear that siblings did recognize inequality among members in sibling relationships but they definitely did not attribute it to sibling term practice. Although there were some who regarded sibling addresses to structure sibling members, they stressed that the ladders of the structure they perceived function not to grant authority but to signify role and to remind everyone of the responsibilities as members of the family.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Attachment, Sibling -- Philippines; Brothers and sisters -- Philippines